DAMPAK PROPAGANDA GERAKAN MENABUNG JEPANG TERHADAP POLA PENYIMPANAN UANG MASYARAKAT INDONESIA (1942-1945) - , MUFIDHA BRILIAN IRIANTI, Dr. Agus Suwignyo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Japan mass mobilization during World War II, has brought some significant impacts for Indonesia. Starting from political and social impacts, it has also affected Indonesian daily life. Japanese occupation was meant to recruit human resources from the region on behalf of Pacific War. Japan made some efforts to attract local citizenâs attentions in every intention to make them cooperate with government programs. For instance, Japanese propaganda are way to communicated with people while the war. It is the program which used a large variety of media to send the messages. According to some sources, Japanese propaganda consisted of program to persuade people made savings in formal institution. In addition, there is a fascinating statement, said that instead of in Nederland decade, bank customers were significantly increased during the Japan period in Indonesia. Thus, there is a presumption about the transformation of saving money method and pattern within local people. As an example, local people started to trust financial institution likewise post office and bank to keep their money. There is also arguing that during that period, the bank customers are dominated by common people instead of bourgeois and aristocracy. It is the concern of this project, to understand the change of peopleâs behavior in saving money, correlated with Japan p ropaganda program in Indonesia, 1942-1945. This research explores the strategy of Japanese propaganda, especially related to saving money persuasion during the occupation. It also describes how people at that period response to deal with it. Another important result which suppose to find is the impact of Japanese saving money propaganda which concern to the changed of people keeping money behavior during the war. However, by describing each of them, this research captures a piece of colonial history in Indonesia that based on daily life aspect. Keyword: Money saving, Japanese period, Propaganda, Indonesia